The Relation between Spatial Organization of the City and Its Function - Al-Hinkawi, Wahda Shuker (Iraqi Journal of Architecture and Planning, 2009)
The city , is one of the expanded and most complex systems that the human beings ever known, as it exist through continuous development and changing process through time. Each generation extends , substitutes , re-arranges and adopts what it inherits before passing with to the new generation, therefore the city can be called in a moment of time as a group of dynamic processes more than being constant facts. The city is a product of a large number of resolutions within its reality, having the small and large measurement to be connected with the social structures and ideological constructions of its occupant, that community creates over time, but remains obscure to the individuals at any moment. The obvious similarity of the cities urban structures overtime and in different parts of the world, indicates to the existence ofmain types ofspatial organization, beyond different structures, which refer to the possibility of building theoretical concepts regarding a spatial theory of the city, through gaining access to the basic logic in creating the physical structures of the city’more over to explain the relation between the city form and its function . The research based on the concept of spaoe in dealing with the urban structure of the city and considered to be the essence in constructive logic, in more specifically building distribution creates a continuous system of spaces that connect buildings in a spatial system that reflects the structure ofthe city, so reaching out to the language that expresses the spatial organization, which requires illustration of the common spatial properties ofthe cities and their differences The research idea, based on these concepts, regarding the space as might provide a common language to the different city forms and some is the relation between the city structure and the method that perlorm its function with Thereby, these concepts were examined in Al - Khadimya fabric, regards as a complete physical system that testified great transformation in its physical, social and functional structure through time. The research, has reached out to explain the relation between the changing in the spatial organization properties of the urban fabric and the natural growh ofthe land use.